An Exploratory Study of India's Foreign Trade Policy During 1990 To 2006: A comprehensive analysis of India's foreign trade policy and its impact on the economy (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Indian economy and outside exchange are on a development direction. Indian fares have made some amazing progress in esteem terms from the season of picking up freedom in 1947. The aggregate estimation of India's stock fares expanded from US 1.3 billion of every 1950-51 to US 63.8 billion of every 2003-04 – a compound rate of 7.6 for each penny. Exchange development has gotten post advancement of 1991. The organization of exchange is currently commanded by produced products and enterprises. India administrations sends out offer in worldwide fares is more than twofold of that of Indian assembling trades. East Asian nations, especially China have turned into a noteworthy exchanging square. There is gigantic undiscovered potential for Indian remote exchange a long time to come.